Managing the Image of the Company Using the Inbound Marketing on the Example of Fan Page - Stopczyńska, Kinga (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Creating a corporate image/brand in the world today is almost the duty of every company. That's what is most important, however, is the fact that it should be the result of the strategy we adopt, and the plan by which the image will be managed. Inbound marketing gives us the opportunity to inspire customers not only with our products, but also to explore the world of our company. A customer who finds it as a permanent part of himself feels the bound with us – treats your company as someone close to him. This special relationship is based on the management, we can create an image using a very popular, but the same demanding medium like fan page. Providing customers with a space where they can exchange views, opinions with other users and provides a great opportunity to create a whole community of people who look at a company in a similar way – a way that we as a company helped to create. The basis for such action is knowledge – about the client, but also about ourselves as a company.